PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN PROBLEM BASED LEARNING UNTUK MENGURANGI KECEMASAN MATEMATIKA DAN MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MTs - Setiani, Ana (Universitas Wiralodra, 2016)
The aims of this research are focused to examine the effect of learning model was estimated to decrease mathematics anxiety and to increase student's mathematical problem solving ability. The instrument that used for this research were ability test of problem solving in math and mathematics quosionaire with likert scale. The data analysis used mixed method embedded konkruen method. Based on data analysis concluded (1) the result show the increasing student's mathematical problem solving ability by problem based learning model better than by expository teaching; (2) increasing quality of studen'ts mathematical problem solving ability by problem based learning better than by expository teaching. (3) significant differences between mathematics anxiety and the accomplisment of student's matematical problem solving ability by problem based learning and by expository teaching (4) significant differences between decreasing mathematics anxiety and increasing of student's mathematical problem solving ability by problem based learning and by expository teaching. and (5) there is significan relationship between mathematics anxiety and the accomplishment of student's mathematical problem solving ability.